2017
DOI: 10.15694/mep.2017.000132
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of peer teaching for medical microbiology lectures

Abstract: Background: A thorough understanding of infectious diseases is needed by medical professionals; therefore effective microbiological teaching is critical. Although faculty lectures are a convenient means of educating large groups of students, they may fail to engage students and convey an understanding of the subject. Therefore, we developed peer teaching methods based on game-based learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…Less commonly covered topics in PAL were pre-clinical or clinical theory: six studies were identified 17,[20][21][22][23][24] , all of which involved senior medical students teaching basic/clinical sciences to pre-clinical (first or second year) students. =…”
Section: Subjects Coveredmentioning
confidence: 99%
“…Less commonly covered topics in PAL were pre-clinical or clinical theory: six studies were identified 17,[20][21][22][23][24] , all of which involved senior medical students teaching basic/clinical sciences to pre-clinical (first or second year) students. =…”
Section: Subjects Coveredmentioning
confidence: 99%
“…Therefore, small group discussion (SGD) was implemented in the organ system part, which focused on application of basic medical knowledge for approaches and managements of patient-based problems, of medical microbiology course in 2016. Moreover, we canceled all peer lectures, taught in 2015, as they were time-consuming for both faculty members and students without any increase in knowledge outcome achievement of students (Ngamskulrungroj et al, 2017). In 2015, each section began with peer/faculty lectures in a large classes followed by peer lectures in small classes.…”
Section: Implementation Of Active Learning Methods In Medical Microbiomentioning
confidence: 99%
“…This teaching method improves students' understanding of the subject and overall satisfaction without compromising the knowledge gain. (Ngamskulrungroj et al, 2017). However, it was still a one-way lecture that mainly focused on memorizing and understanding the subject and too time consuming for both students and faculty members (Ngamskulrungroj et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations